Update on diagnosis and management of childhood epilepsies - Sameer M. Zuberi; Joseph D. Symonds (Brazilian Society of Pediatrics, 2015)
Objectives: To review the current evidence base for the diagnosis and management of the childhood epilepsies and to draw attention to the current gaps in this evidence base. The focus will be on therapeutic aspects. Current International League Against Epilepsy (ILAE) terminology will be described and used throughout the discussion. The review will draw attention to recent advances that have been made in both our understanding and treatment of the childhood epilepsies. Potential future directions for research and treatment options will be discussed. Sources: Original articles relevant to the subject were obtained from the MedLine database using pertinent MeSH terms. Relevant papers were read and assimilated. Citation searching was used. Summary of the findings: Epilepsy is a major cause of global disease burden. Childhood epilepsies are a heterogeneous group of conditions. A multi‐axial diagnostic approach should be taken prior to making treatment and management decisions for any individual patient. For the majority of patients, successful control of seizures can be achieved with a single medication. However, a significant minority develops refractory disease. Epilepsy surgery can provide cure for a carefully selected group of these cases. Conclusions: There remain significant gaps the evidence base for treatment in several areas of childhood epilepsy. Concerted multi‐center efforts should be made to try to close these gaps. A personalized medicine approach may help to reduce the proportion of refectory cases of childhood epilepsy in future.